2012
DOI: 10.1111/j.1442-2050.2012.01439.x
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative outcomes of esophagectomy preceded by the laparoscopic transhiatal approach for esophageal cancer

Abstract: This study was designed to determine the efficacy of esophagectomy preceded by the laparoscopic transhiatal approach (LTHA) with regard to the perioperative outcomes of esophageal cancer. The esophageal hiatus was opened by hand-assisted laparoscopic surgery, and carbon dioxide was introduced into the mediastinum. Dissection of the distal esophagus was performed up to the level of the tracheal bifurcation. En bloc dissection of the posterior mediastinal lymph nodes was performed using LTHA. Next, cervical lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 24 publications
1
22
1
Order By: Relevance
“…Furthermore, our results demonstrated that the total intraoperative blood loss was significantly decreased and the duration of thoracic drainage was significantly shortened using LTHA. We consider that one of the reasons is that this method enables dissection of the appropriate layer under a magnified videoscopic view and, therefore, damage to the microvessels and lymphatic ducts is avoided (8,9). In our experience, there were no problems associated with applying a 10-mmHg pneumomediastinum pressure for intraoperative respiratory care.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…Furthermore, our results demonstrated that the total intraoperative blood loss was significantly decreased and the duration of thoracic drainage was significantly shortened using LTHA. We consider that one of the reasons is that this method enables dissection of the appropriate layer under a magnified videoscopic view and, therefore, damage to the microvessels and lymphatic ducts is avoided (8,9). In our experience, there were no problems associated with applying a 10-mmHg pneumomediastinum pressure for intraoperative respiratory care.…”
Section: Discussionmentioning
confidence: 75%
“…The scopist stood near the patient's groin. Carbon dioxide was introduced into the intra-abdominal space and the pneumoperitoneum pressure was controlled at 10 mmHg (8)(9)(10)(11).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations